IDEAPHORIA : Faculty of Applied and Creative Arts, eBulletin, Vol.7, 2023 - Terry, Lucas (Faculty of Applied and Creative Arts, 2023)
Faculty of Applied and Creative Arts (FACA) students from the Animation programme showcased their creative works at the international level, namely the Student World Impact Film Festival (SWIFF) 2023 (USA), The Brazosport Arts in Media (BAM!) Festival 2023 (USA), and Australia Animation Film Festival (AniMate) 2024 (Australia).